2016
DOI: 10.1038/gene.2016.38
|View full text |Cite
|
Sign up to set email alerts
|

Fecal metabolomics in pediatric spondyloarthritis implicate decreased metabolic diversity and altered tryptophan metabolism as pathogenic factors

Abstract: Objective We have previously shown alterations in the composition of the gut microbiota in children with enthesitis-related arthritis (ERA). To explore the mechanisms by which an altered microbiota might predispose to arthritis, we performed metabolomic profiling of fecal samples of children with ERA. Methods Fecal samples were collected from two cohorts of children with ERA and healthy control subjects. Nano-liquid chromatography – mass spectroscopy (LC-MS) was performed on the fecal water homogenates with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 36 publications
3
50
1
1
Order By: Relevance
“…Additionally, in a cohort of patients with the enthesitis‐related arthritis (ERA) subtype of JIA compared to healthy controls, differences in community structure were predicted to decrease metabolic functions. In the same cohort, a lower diversity of ions and underrepresentation of the tryptophan metabolic pathway was observed in patients . Tryptophan metabolites can lead to the production of proinflammatory cytokines, thus potentially linking the gut microbiota with inflammation .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Additionally, in a cohort of patients with the enthesitis‐related arthritis (ERA) subtype of JIA compared to healthy controls, differences in community structure were predicted to decrease metabolic functions. In the same cohort, a lower diversity of ions and underrepresentation of the tryptophan metabolic pathway was observed in patients . Tryptophan metabolites can lead to the production of proinflammatory cytokines, thus potentially linking the gut microbiota with inflammation .…”
Section: Discussionmentioning
confidence: 77%
“…In the same cohort, a lower diversity of ions and underrepresentation of the tryptophan metabolic pathway was observed in patients . Tryptophan metabolites can lead to the production of proinflammatory cytokines, thus potentially linking the gut microbiota with inflammation . In another cohort of ERA patients, predicted functions of the gut microbiota were related to cell motility and chemotaxis .…”
Section: Discussionmentioning
confidence: 83%
“…These analyses revealed an under‐representation of multiple metabolic pathways, including the tryptophan metabolism pathway. Significantly fewer microbial genes associated with metabolic processes in the patients compared with the controls were observed, indicating diminished metabolic diversity as a potential feature of JIA‐ERA …”
Section: Role Of Microbiota and Efficacy Of Therapeutics In Jiamentioning
confidence: 96%
“…Significantly fewer microbial genes associated with metabolic processes in the patients compared with the controls were observed, indicating diminished metabolic diversity as a potential feature of JIA-ERA. 80 A study in an Italian cohort of 29 patients with JIA (19 with JIA-ERA and 10 with JIA-non ERA) in comparison to 29 healthy controls, identified differences in various bacterial families belonging to the Firmicutes phyla. 81 In particular, in comparison to healthy subjects, Ruminococcaceae resulted as increased in patients with JIA, Veillonellaceae in JIA-non ERA, whereas Clostridiaceae and Peptostreptococcaceae were decreased in JIA-ERA.…”
Section: Microbiota and Jia Susceptibilitymentioning
confidence: 99%
“…This could result in decreased production of butyrate, which is an important substrate for gut epithelial cells and can also directly induce the differentiation of regulatory T cells . It is thus of particular interest that Stoll et al also demonstrated decreased microbial genetic potential to synthesize butyrate as well as decreased fecal water representation of the butyrate pathway …”
Section: Microbiota Alterations In Jiamentioning
confidence: 99%